2018
DOI: 10.3390/en11061442
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Wind Turbine Wakes under Various Atmospheric Conditions

Abstract: Abstract:We present a numerical study of two utility-scale 5-MW turbines separated by seven rotor diameters. The effects of the atmospheric boundary layer flow on the turbine performance were assessed using large-eddy simulations. We found that the surface roughness and the atmospheric stability states had a profound effect on the wake diffusion and the Reynolds stresses. In the upstream turbine case, high surface roughness increased the wind shear, accelerating the decay of the wake deficit and increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As a general rule of thumb [35,36], the stronger the ambient turbulent intensity, the faster the wake recovery. Some wind tunnel experiments and CFD simulations [37,38] have shown that the turbulence intensity in the wake overlay area is higher than that of the undisturbed wind turbine at the same location. Meanwhile, as mentioned above, for a particular experiment of two turbines in a row, the wake velocity of the downwind turbine recovers Energies 2019, 12, 680 5 of 14 more rapidly than that of the upwind one.…”
Section: Wake Superpositionmentioning
confidence: 99%
“…As a general rule of thumb [35,36], the stronger the ambient turbulent intensity, the faster the wake recovery. Some wind tunnel experiments and CFD simulations [37,38] have shown that the turbulence intensity in the wake overlay area is higher than that of the undisturbed wind turbine at the same location. Meanwhile, as mentioned above, for a particular experiment of two turbines in a row, the wake velocity of the downwind turbine recovers Energies 2019, 12, 680 5 of 14 more rapidly than that of the upwind one.…”
Section: Wake Superpositionmentioning
confidence: 99%
“…Wakes of large offshore wind farm clusters over distances of more than 10 km were first observed using data from satellite SAR (Christiansen and Hasager, 2005). Li and Lehner (2013) and Hasager et al (2015) analysed offshore wind farm wakes using SAR images and compared the long, visible wakes to results of mesoscale models. Nygaard and Hansen (2016) analysed the power production of an offshore wind farm before and after the commissioning of a wind farm located 3 km to the west on the basis of SCADA data and discovered power losses caused by wakes of the upstream wind farm in the first rows of the downstream wind farm.…”
Section: Introductionmentioning
confidence: 99%
“…in warm air over cold water, wake deficits can last far downstream. Hansen et al (2011), Dörenkämper et al (2015) and Lee et al (2018) investigated wake recovery with respect to atmospheric stability and found an increased length of wakes in stable stratification. Emeis (2009), Turner et al (2014) and Schmidt and Stoevesandt (2015) suggested optimized wind farm layouts to reduce wake effects on the basis of the prevailing wind rose and stability distribution.…”
Section: Introductionmentioning
confidence: 99%